Prophylactic amnioinfusion in oligohydramnios - T., Dhiviya Narbhavi; J., Cicily T.; S., Kala B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Oligohydramnios causes many intrapartum maternal and fetal complications. Intrapartum amnioinfusion effectively increases amniotic fluid volume and thereby decreases FH decelerations. The objective of this study was to compare the frequency of fetal heart decelerations and its perinatal outcome with and without amnioinfusion in patients with oligohydramnios and the cesarean rates for fetal distress between them. Methods: In study group, 100 patients in labour with AFI < 5 cm, oligohydramnios and IUGR with normal doppler, postdated pregnancies with AFI ≤ 5 cm with normal doppler were selected and prophylactic amnioinfusion with 300 ml lukewarm saline is given aseptically for 15 minutes after amniotomy. Continuous CTG monitoring done till delivery. If FH decelerations occur, the bolus was repeated up to 3 times. 100 age matched controls managed with conventional methods without amnioinfusion were selected retrospectively from labour room case records. Results: Incidence of FH decelerations was lower in study group (59% versus 84%). Cesarean section for fetal distress was reduced (20.9% versus 79.1%) Perinatal outcome was better. Babies with normal 1-minute Apgar was 86% compared to 75% in controls. Frequency of FH decelerations was reduced (20% versus 73%). Occurrence of 2 FH decelerations were 13% versus 33%, 3 FH decelerations were 7% versus 27% and > 3 times was 0% versus 13%. Conclusions: Prophylactic amnioinfusion can easily and effectively reduce the FH decelerations and caesarean section rate for fetal distress in oligohydramnios improving both maternal and fetal outcomes with negligible risks.